BRIDGING THE GAP BETWEEN SEIZURE CONTROL AND QUALITY OF LIFE: STIRIPENTOL AND FENFLURAMINE IN DRAVET SYNDROME - Katarzyna Kozon,; Katarzyna Krupa,; Patrycja Fiertek,; Adrianna Brzozowska,; Karolina Niewczas,; Aleksandra Gradek,; Katarzyna Herjan,; Piotr Armański,; Patryk Pustuła,; Marcin Sawczuk, (International Journal of Innovative Technologies in Social Science, 2025)
Dravet syndrome is a severe, early childhood epileptic encephalopathy, most often associated with a mutation in the SCN1a gene characterized by drug resistance and high neurological burden. For many years treatment was limited to non-specific antiepileptic drugs, but recently new, targeted therapies have appeared, which have significantly improved the prognosis of patients. Stiripentol, modulating GABAergic transmission, has been approved as an adjuctive treatment in the treatment of Dravet syndrome, showing a significant reduction in the frequency of seizures in combination with clobazam and valproic acid. In turn, fenfluramine, acting on serotonin receptors, among others, has proven also effective. Both drugs have been approved by the FDA and EMA, constitiuting a breakthrough in the treatment of Dravet syndrome Their introduction has significantly improved the quality of life of patients and opened up new perspectives in the treatment of developmental epilepsies.